Values of ecosystem services in the physical characteristics of campus's courtyard - Rosli, Nur Diana Shafika; Harun, Nor Zalina; Ibrahim, Putri Haryati (2016)
Courtyards in university offer multiple ecosystem services (ES), providing a variety of benefits to human well-being. Ecosystem services are the benefits people obtain from ecosystems. It is the conditions and processes through which natural ecosystems and the species are to sustain and fulfill human life. The planning of courtyards is a powerful way for determining and shaping the living environment of any area in campus. It also works as joints for surrounding environment and provide support to academic and students learning life within the campus. Nonetheless, there are issues addressing the weakness and limitations of landscape design and planning of courtyards in campus. For instance, it is discovered that campus open space designs have been treated as leftover space of a building resulting to courtyard becoming less meaningful for students’ in campus. This paper is aimed to study the ecosystem services in campus courtyard. Hence, the objectives of this research are to study the physical characteristic of campus courtyard as student learning area, to study the contribution of ecosystem services provided by campus courtyard, to identify campus courtyard typologies that can be linked to ecosystem services. This is to understand how knowledge on ecosystem service can improve campus courtyard to be an academic and student learning activities. The research methods used consisted of a content analysis and survey on courtyard physical characteristics and space use in campus. A total of 300 respondents for survey were included among students in campus. The findings of this research are to reveal the aspects of courtyard typologies in relation to the ecosystem services. The research found that the physical development and planning of courtyard in campus indicates poor environment for students and users. Thus, design guidelines on courtyards’ connection to the values of ecosystem services were proposed in the paper. Above all, this approach to understand the ecosystem services of courtyards’ campus is a comprehensive approach to communicate the important of courtyard landscape design within campus.